Latin American history - Wilgus, A. Curtis (Alva Curtis) 1897-1981.; d'Ega, Raul. (New York Barnes & Noble, 1963)
A summary of political, economic, social, and cultural events from 1492 to the present
Previous edition published under title: An outline-history of Latin America.
Includes bibliographical references and index.
Keywords: Latin America -- History -- Outline, syllabi, etc